Review of instrumental texture measurements as phenotypic tool to assess textural diversity of root, tuber and banana food products - Ayetigbo, O.; Arufe, S.; Kouassi, A.; Adinsi, L.; Adesokan, M.; Escobar, A.; Delgado, L.F.; Tanimola, A.; Oroniran, O.; Vepowo, C.K.; Nakitto, M.; Khakasa, E.; et al. (Wiley, 2024)
Roots, tubers and bananas (RTBs) contribute immensely to food security and livelihoods in sub-Saharan Africa, Asia and Latin America. The adoption of RTB genotypes in these regions relies on the interplay among agronomic traits, ease of processing and consumer preference. In breeding RTBs, until recently, little attention was accorded key textural traits preferred by consumers. Moreover, a lack of standard, discriminant, repeatable protocols that can be used to measure the textural traits deter linkages between breeding better RTB genotypes and end user/consumer's preferences. RTB products texture i.e. behaviour of RTB food products under unique deformations, such as disintegration and the flow of a food under force - is a critical component of these preferences. The preferences consumers have for certain product texture can be evaluated from expert sensory panel and consumer surveys, which are useful tools in setting thresholds for textural traits, and inform breeders on what to improve in the quality of RTBs. Textural characterization of RTBs under standard operating procedures (SOPs) is important in ensuring the standardization of texture measurement conditions, predictability of textural quality of RTBs, and ultimately definition of RTB food product profiles (FPPs). This paper reviews current SOPs for the textural characterization of RTBs, including their various associated methods, parameters, challenges and merits. Case studies of texture characterized during development of SOPs and evaluation of texture of RTB populations is discussed and insights into key textural attributes and correlations between instrumental, sensory and consumer assessment of texture unique to various RTB food products. Hardness was considered a universal key textural attribute to discriminate RTBs. The review should provide adequate insight into texture of RTB food products and critical factors in their measurement. It aims to promote inclusion of texture in breeding pipelines by investigating which textural traits are prioritized by consumers, particularly since the inclusion of textural traits is recently gaining prominence by breeders in improving RTBs.